Impacts of snow on soil temperature observed across the circumpolar north - Yu Zhang; Artem B Sherstiukov; Budong Qian; Steven V Kokelj; Trevor C Lantz (Environmental Research Letters, 2018)
Climate warming has significant impacts on permafrost, infrastructure and soil organic carbon at the northern high latitudes. These impacts are mainly driven by changes in soil temperature (T _S ). Snow insulation can cause significant differences between T _S and air temperature (T _A ), and our understanding about this effect through space and time is currently limited. In this study, we compiled soil and air temperature observations (measured at about 0.2 m depth and 2 m height, respectively) at 588 sites from climate stations and boreholes across the northern high latitudes. Analysis of this circumpolar dataset demonstrates the large offset between mean T _S and T _A in the low arctic and northern boreal regions. The offset decreases both northward and southward due to changes in snow conditions. Correlation analysis shows that the coupling between annual T _S and T _A is weaker, and the response of annual T _S to changes in T _A is smaller in boreal regions than in the arctic and the northern temperate regions. Consequently, the inter-annual variation and the increasing trends of annual T _S are smaller than that of T _A in boreal regions. The systematic and significant differences in the relationship between T _S and T _A across the circumpolar north is important for understanding and assessing the impacts of climate change and for reconstruction of historical climate based on ground temperature profiles for the northern high latitudes.